2015
DOI: 10.1002/ange.201504076
|View full text |Cite
|
Sign up to set email alerts
|

The Cleavage of a CC Bond in Cyclobutylanilines by Visible‐Light Photoredox Catalysis: Development of a [4+2] Annulation Method

Abstract: Abstract:We report the first example of an intermolecular [4+ +2] annulation of cyclobutylanilines with alkynes enabled by visible-light photocatalysis.M onocyclic and bicyclic cyclobutylanilines successfully undergo the annulation with terminal and internal alkynes to generate aw ide variety of aminesubstituted cyclohexenes including new hydrindan and decalin derivatives with good to excellent diastereoselectivity.T he reaction is overall redox neutral with perfect atom economy.The release of ring strain has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 64 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…The development of methods for the selective functionalisation of non-activated sp 3 carbon atoms is al ongstanding endeavour in organic synthesis. [1] Radical strategies are attractive options owing to the ability of odd-electron species to undergo transposition processes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The development of methods for the selective functionalisation of non-activated sp 3 carbon atoms is al ongstanding endeavour in organic synthesis. [1] Radical strategies are attractive options owing to the ability of odd-electron species to undergo transposition processes.…”
mentioning
confidence: 99%
“…[1] Radical strategies are attractive options owing to the ability of odd-electron species to undergo transposition processes. [2] If as uitably reactive radical is generated in as pecific position of an organic molecule,t hen C(sp 3 ) À C(sp 3 )a nd C(sp 3 ) À Hb ond cleavage can be triggered, leading to remote functionalisations.C lassical examples are the ring opening of a-cyclopropyl radicals (radical clock) [3] and the 1,5-hydrogen atom abstraction of nitrogen radicals-the key step of the Hofmann-Lçffler-Freytag (HLF) reaction [4] (Scheme 1A). [5] We have recently developed two classes of oximes that provide access to iminyl radicals by both reductive and oxidative visible-light-mediated single electron transfer (SET) and employed them in intramolecular cyclisation processes (Scheme 1B).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[7] Zheng and coworkers have demonstrated that cyclopropylanilines and cyclobutylanilines can be oxidized to a radical cation species I using photoredox catalysis (Scheme 1 C). [8] After ring opening, the resulting iminium radical II underwent (3+2) annulation with alkenes or alkynes. Our group later extended this approach to cyclopropenes, [9] and Stephenson and coworkers applied it to the synthesis of 1-aminonorbornanes.…”
mentioning
confidence: 99%